The safety and efficacy of cobimetinib for the treatment of BRAF V600E or V600K melanoma. Issue 7 (2nd July 2016) - Amaral, Teresa; Nouri, Noura; Garbe, Claus
ABSTRACT: Introduction : In the recent years, melanoma patients' outcome and survival improved, mainly because of systemic treatment improvement with targeted therapy and checkpoint blockade. Targeted therapy with BRAF and MEK inhibitors was approved to treat patients with unresectable or metastatic melanoma, harboring BRAF V600 mutations. This paper addresses the safety and efficacy of cobimetinib, when used in combination with vemurafenib, in the previous mentioned setting. Areas covered : This article presents an overview on the rationale for clinical development of cobimetinib, as well as the mechanism of action, the efficacy and safety, and the most important trials that led to the approval of the combination therapy with vemurafenib. We searched the PubMed for published papers related to safety and efficacy of cobimetinib, and resistance mechanisms to BRAF inhibition. The abstract databases of the American Society of Clinical Oncology and European Society for Medical Oncology were also searched for updates on the mentioned clinical trials. Expert commentary : Patients treated with targeted therapy experience a rapid tumor response. However, virtually all patients will develop resistance to treatment. Therapeutic combinations to overcome resistance mechanisms are currently addressed. In the future, targeted therapy strategy will include three or more drugs, probably from different therapeutic classes.